Evaluation of umami taste in mushroom extracts by chemical analysis, sensory evaluation, and an electronic tongue system. (1st February 2016) - Phat, Chanvorleak; Moon, BoKyung; Lee, Chan
Highlights: Mushrooms were analysed for umami taste characteristic using HPLC and sensory evaluations. Equivalent umami concentration ( EUC ) was examined, and most mushrooms exhibited high EUC values. The EUC and the sensory score from the electronic tongue test were highly correlated. The EUC also showed significant correlation with the human sensory evaluation score. All three analysis methods provide comparable results and can be used equivalently. Abstract: Seventeen edible mushrooms commercially available in Korea were analysed for their umami taste compounds (5′-nucleotides: AMP, GMP, IMP, UMP, XMP; free amino acids: aspartic, glutamic acid) and subjected to human sensory evaluation and electronic tongue measurements. Amanita virgineoides featured the highest total 5′-nucleotide content (36.9 ± 1.50 mg/g), while monosodium glutamate-like components (42.4 ± 6.90 mg/g) were highest in Agaricus bisporus . The equivalent umami concentration ( EUC ) ranged from 1.51 ± 0.42 to 3890 ± 833 mg MSG/g dry weight; most mushrooms exhibited a high umami taste. Pleurotus ostreatus scored the highest in the human sensory evaluation, while Flammulina velutipes obtained the maximum score in the electronic tongue measurement. The EUC and the sensory score from the electronic tongue test were highly correlated, and also showed significant correlation with the human sensory evaluation score. These results suggest that the electronic tongue is suitable to determine the characteristic umami taste of mushrooms.